Microprocessors a programmer's view - Dewar, Robert B. K. (McGraw-Hill, 1990)
This book is suitable for an advanced level course which is concerned with comparing and contrasting the many competing microprocessor designs currently available. It concentrates on the interesting features that distinguish the most important chips and emphasises the comparison of RISC (Reduced Instruction Set Computer) and CISC (Complete Instruction Set Computer) chips.